Validasi Metode Analisis Zeatin Menggunakan Teknik Ultra High Performance Liquid Chromatography (UHPLC) sebagai Instrumen Studi Kultur In vitro Kelapa Sawit (Elaeis guineensis Jacq.) - Arfan Nazhri Simamora; Diny Dinarti; Sudarsono Sudarsono (Jurnal Penelitian Kelapa Sawit, 2020)
Quantitative analysis of zeatin is needed to determine correlation between callus and embryo formation with the presence of zeatin itself on explant and interaction between zeatin content on explant and synthetic plant growth regulators (PGRs) which is added to oil palm in vitro culture media. This research was conducted to obtain method of zeatin content analysis that is easy and fast to reproduce, so it can be applied to research studies on phytohormones, especially zeatin. The analysis was carried out using ultra high performance liquid chromatography (UHPLC) with C18 column and isocratically 100% methanol mobile phase and 0.2 mL / minute flow rate with UV detector at length λ = 280 nm. Analyzed explants were taken from individuals representing La Me, Avros, PPKS 239 and Simalungun varieties. Results of system suitability test indicated that the method fulfilled its requirements to be used for analysis with relative standard deviation (RSD) value was ≤ 2. Method validation gaveresults of calibration curve with the coefficient of determination r2 = 0,9996 and precision of instrument and method obtained relative standard deviation by 0,56 and 1,03, respectively. LoD and LoQ values ​​obtained were 2,457 ppm and 7,446 ppm respectively.